2023
DOI: 10.3389/fbioe.2023.1127166
|View full text |Cite
|
Sign up to set email alerts
|

Biochar: An effective measure to strengthen phosphorus solubilizing microorganisms for remediation of heavy metal pollution in soil

Abstract: Introduction: Phosphorus solubilizing microbial remediation is a sustainable technology for soil heavy metal remediation 1.1 Microbial remediation is an effective measure to achieve sustainable remediation of heavy metals in soil Heavy metals (HMs) pollution of soil caused by human activities is a serious threat to human health and sustainable social development. The insidious, lagging, long-term, inhomogeneous and irreversible nature of heavy metal pollution has led to serious degradation of soil ecological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Studies have shown that PSMs have a good fixation effect on heavy metal ions, such as Cr 6+ , Co 2+ , Cd 2+ , Zn 2+ , Cu 2+ , and Pb 2+ in soil (Qian et al, 2019;Hu and Chen, 2023). PSMs can first dissolve insoluble phosphorus sources by releasing organic acids and enzymes and converting them to PO 4 3− which binds to heavy metals to form phosphate precipitates and can greatly reduce the amount of free heavy metal ions in the soil (Chen et al, 2023). Second, PSM can secrete organic acids, indoleacetic acids, iron carriers, and other substances with oxidizing or reducing properties, thereby altering the metal valence state and diminishing the toxicity of toxic metals (Lai et al, 2022;Yu et al, 2022).…”
Section: Psms Can Repair Heavy Metal Pollution In Urban and Rural Soilmentioning
confidence: 99%
“…Studies have shown that PSMs have a good fixation effect on heavy metal ions, such as Cr 6+ , Co 2+ , Cd 2+ , Zn 2+ , Cu 2+ , and Pb 2+ in soil (Qian et al, 2019;Hu and Chen, 2023). PSMs can first dissolve insoluble phosphorus sources by releasing organic acids and enzymes and converting them to PO 4 3− which binds to heavy metals to form phosphate precipitates and can greatly reduce the amount of free heavy metal ions in the soil (Chen et al, 2023). Second, PSM can secrete organic acids, indoleacetic acids, iron carriers, and other substances with oxidizing or reducing properties, thereby altering the metal valence state and diminishing the toxicity of toxic metals (Lai et al, 2022;Yu et al, 2022).…”
Section: Psms Can Repair Heavy Metal Pollution In Urban and Rural Soilmentioning
confidence: 99%
“…PSM plays a vital role in all three main processes that affect the soil phosphorus content [dissolution-precipitation, adsorption-desorption, and mineralization-immobilization (Sharma et al, 2013 )]. It is worth noting that PSMs with high heavy metal resistance can alleviate HMs toxicity and the accumulation of HMs in plants through a range of mechanisms (Ahemad, 2015 ; Chen et al, 2023 ; Figure 1 ). In general, the tolerance of PSM to HMs is related to the isolation environment of the strain.…”
Section: The Remediation Function Of Hms Pollution By Phosphate Solub...mentioning
confidence: 99%
“…PSM mainly remediates heavy metal contaminated soil through bioadsorption and enrichment, biotransformation, and bioprecipitation (Chen et al, 2023 ). Firstly, PSM can reduce the bioavailability of HMs by synthesizing metal-binding proteins (such as metallothionein) and releasing siderophores to chelate HMs and accumulate them in the cells (Gupta and Kumar, 2017 ).…”
Section: The Remediation Function Of Hms Pollution By Phosphate Solub...mentioning
confidence: 99%
“…6) The use of phosphate solubilizing microorganisms can also reduce the use of chemical fertilizers and pesticides, reducing the negative impact on the environment (Ahemad, 2015). In addition, the good affinity of PSM allows it to be used together with other materials to improve soil properties and remediate environmental pollution (Chen et al, 2019;Feng et al, 2022;Lai et al, 2022;Chen et al, 2023a).…”
Section: Phosphate Solubilizing Microorganisms As a Green Technology ...mentioning
confidence: 99%